2014
DOI: 10.1007/s11934-014-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy for Treatment of Upper Urinary Tract Stones in Children: Technical Considerations

Abstract: The incidence of pediatric urolithiasis is increasing. While many smaller stones may pass spontaneously, surgical therapy is sometimes warranted. Surgical options include shock wave lithotripsy, ureteroscopy, percutaneous nephrolithotomy, and open surgery. Ureteroscopy represents a minimally invasive approach, and it is increasingly being used to treat pediatric upper tract calculi. Ureteroscopy is performed under anesthesia and fluoroscopic guidance, with basket extraction or lithotripsy of the calculi. Techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(39 reference statements)
0
5
0
2
Order By: Relevance
“…They reported an 83.3% stone clearance with single session PCNL, with only one procedure being abandoned due to [14][15][16], with no children requiring blood transfusion [9]. Zeng et al reported their experience of children in 331 renal units, with stone clearance rates reaching 80.4% and blood transfusion rates of 3.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported an 83.3% stone clearance with single session PCNL, with only one procedure being abandoned due to [14][15][16], with no children requiring blood transfusion [9]. Zeng et al reported their experience of children in 331 renal units, with stone clearance rates reaching 80.4% and blood transfusion rates of 3.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The patient population also includes children as young as one year, where ureteroscopy may be contraindicated. Semi-rigid ureteroscopy could be used for renal pelvic or upper pole stones and, in carefully selected cases, flexible ureteroscopy may be beneficial [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the light of these results, the authors reported that RIRS is superior to mini-perc in stones less than 2 cm in size, but that miniperc has a better success rate with larger stones, and that RIRS can represent an alternative to it. As technology has advanced, thinner and more resistant ureteroscopes and lithotripters with a greater deflection capacity and image quality have been developed [31] . This has made it easier to break stones at all points in the kidney.…”
mentioning
confidence: 99%
“…Cada vez se utiliza más, pero aún hay grupos no habituados con la endourología preocupados por las potenciales complicaciones de isquemia y estenosis ureteral, perforación o RVU a pesar de que se han descrito muy pocas 9 . En la literatura se describe un porcentaje de complicación entre 0-15% 3 .…”
Section: Discussionunclassified
“…En niños, a diferencia del manejo en adultos, donde recomienda tratamiento médico con alfalíticos y valoración de implantación de doble J en litiasis ureterales 16 para evitar impactación y sobreinfección de la litiasis, nosotros realizamos URS sin haber presentado ningún cuadro séptico secundario. El mayor avance en la URS fue la miniaturización del instrumental, lo que nos ha permitido aconsejarlo como primera opción terapéutica 5,9,17 . Vilches et al 18 han demostrado en su estudio aleatorizado mejores resultados en adultos de la URS frente a la LEOC en litiasis de polo inferior, especialmente para el tamaño entre 10 y 15 mm.…”
Section: Discussionunclassified